Tuning the Optical Response of Photonic Bandgap Structures 2004
DOI: 10.1117/12.560927
|View full text |Cite
|
Sign up to set email alerts
|

Strain-tunable photonic bandgap microcavity waveguides in silicon at 1.55 μm

Abstract: The majority of photonic crystals developed till-date are not dynamically tunable, especially in silicon-based structures. Dynamic tunability is required not only for reconfiguration of the optical characteristics based on user-demand, but also for compensation against external disturbances and relaxation of tight device fabrication tolerances. Recent developments in photonic crystals have suggested interesting possibilities for static small-strain modulations to affect the optical characteristics 1-3 , includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There have been only a small number of reports on strain measurement via stretching of a PC. Wong et al [13] analytically examined wavelength shifts at strains of up to 0.2%, while Stomeo et al [14] predicted 5.82 nm of wavelength shift for every GPa of applied unidirectional pressure. Ying et al [15] demonstrated a wavelength shift of 212 nm under 20 kPa of applied stress in thin photonic band gap composite films, corresponding to more than 20% and 30% of tensile and compressive strains, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been only a small number of reports on strain measurement via stretching of a PC. Wong et al [13] analytically examined wavelength shifts at strains of up to 0.2%, while Stomeo et al [14] predicted 5.82 nm of wavelength shift for every GPa of applied unidirectional pressure. Ying et al [15] demonstrated a wavelength shift of 212 nm under 20 kPa of applied stress in thin photonic band gap composite films, corresponding to more than 20% and 30% of tensile and compressive strains, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Deformation can be induced in a variety of ways, including mechanical [2,3], thermal, and electrostatic actuation [10] as well as through the use of piezoelectric material [12,13]. There have been only a small number of reports on strain measurement via stretching of a PC.…”
Section: Introductionmentioning
confidence: 99%
“…This type of perturbation has been studied theoretically [RH08; EG13; DL14a] and models effects such as uneven thermal [DWN+11; DLT+04] or uneven strain tuning [WYR+04]. Quite naturally, the first task in the study of the perturbed Maxwell operator M λ = M w(λ) is to derive effective dynamics, i. e. to relate the perturbed to the unperturbed dynamics if one knows something about the initial states.…”
Section: The Maxwell-harper Approximation For Non-gyrotropic Phcsmentioning
confidence: 99%
“…The small dimensionless parameter λ 1 relates the scale of the lattice to the scale of the macroscopic modulation. The scalar modulation functions τ and τ µ describe an isotropic perturbation of the matrix-valued material weights and µ which may be induced by uneven thermal [DWN+11; DLT+04] or strain tuning [WYR+04].…”
mentioning
confidence: 99%